Financial-transaction tax: small is beautiful - Zsolt Darvas; Jakob von Weizsäcker (Bruegel, 2010)
Resident Fellows Zsolt Darvas and Jakob von Weizsäcker wrote this paper on the pros and cons of a Financial Transaction Tax (FTT) following testimony von Weizsäcker gave for the Economic and Monetary Affairs Committee of the European Parliament. They argue that a small tax on financial transactions is justifiable in order to limit socially undesirable transactions.
Keywords: 330; Kapitalverkehrsteuer; Kapitalverkehrspolitik; Kapitalmobilität; Internalisierung externer Effekte; Welt